2019
DOI: 10.1097/rlu.0000000000002508
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Response to Lower Dose of 177Lu-PSMA-617 in a Metastatic Castration–Resistant Prostate Cancer Patient With a Transplanted Kidney

Abstract: A 68-year-old man with metastatic castration-resistant prostate cancer and widespread bone metastases as well as a history of kidney transplant, underwent 5 cycles of 177Lu–prostate-specific membrane antigen 617 therapies in our department. Being more cautious of the radiation burden imposed on the transplanted kidney, a lower average dose of 4 GBq per cycle was administered (instead of the more routine 6.0-7.4 GBq per cycle). However, excellent response was noted and serum creatinine level of 0.8 mg/dL remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The role of PSMA-RLT in hormone-sensitive prostate cancer has however not been investigated extensively, and only anecdotal studies exist in literature on the role of PSMA-RLT as a first-line therapy in oligometastatic hormone-sensitive prostate cancer. PSMA-RLTs have been found to be more effective in low-volume disease due to high uptake of radioligands in smaller lesions [7][8][9]. This index case highlights the potential role of PSMA-RLT in treatment-naive patients where a single dose of PSMA-RLT was able to achieve a complete biochemical and radiological response in a patient of oligometastatic hormone-sensitive prostate cancer with no significant toxicity.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The role of PSMA-RLT in hormone-sensitive prostate cancer has however not been investigated extensively, and only anecdotal studies exist in literature on the role of PSMA-RLT as a first-line therapy in oligometastatic hormone-sensitive prostate cancer. PSMA-RLTs have been found to be more effective in low-volume disease due to high uptake of radioligands in smaller lesions [7][8][9]. This index case highlights the potential role of PSMA-RLT in treatment-naive patients where a single dose of PSMA-RLT was able to achieve a complete biochemical and radiological response in a patient of oligometastatic hormone-sensitive prostate cancer with no significant toxicity.…”
mentioning
confidence: 77%
“…PSMA-RLTs have been found to be more effective in low-volume disease due to high uptake of radioligands in smaller lesions. [7][8][9] This index case highlights the potential role of PSMA-RLT in treatment-naive patients where a single dose of PSMA-RLT was able to achieve a complete biochemical and radiological response in a patient of oligometastatic hormone-sensitive prostate cancer with no significant toxicity. The case also highlights the enhanced efficacy of PSMA-RLT in low-volume disease, possibly due to higher bioavailability of the radioligands in smaller lesions.…”
mentioning
confidence: 87%
“…A recent phase III trial group study used 7.4 GBq (200 mCi). A study by Norouzi et al 9 shows excellent response to a low dose of 177 Lu-PSMA therapy in transplant kidney. Another recent study by Zhang et al 10 reported that 177 Lu-PSMA therapy is feasible, effective, and well tolerated, without any signs of acute or subacute nephrotoxicity in a single functioning kidney.…”
mentioning
confidence: 99%
“…[2][3][4][5][6] The mCRPC patients with transplant kidney or end-stage renal disease receive lower than full dose of 177 Lu-PSMA, thereby preventing optimum therapeutic effect. 7,8 There is a dearth of literature for use of RLT in mCRPC patients with transplant kidney. This case report shows the efficacy of full dose of 177 Lu-PSMA RLT as an alternate option to nephrotoxic chemotherapy in mCRPC patients with renal transplant.…”
mentioning
confidence: 99%
“…177 Lu-PSMA is safe in mCRPC patients with impaired renal function and single functioning kidney with only a slight (~1%) risk of radiation-induced nephropathy 2–6 . The mCRPC patients with transplant kidney or end-stage renal disease receive lower than full dose of 177 Lu-PSMA, thereby preventing optimum therapeutic effect 7,8 . There is a dearth of literature for use of RLT in mCRPC patients with transplant kidney.…”
mentioning
confidence: 99%